2007
DOI: 10.1038/sj.eye.6702999
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between refraction and allergic conjunctivitis

Abstract: Purpose External allergens are the main causative factor in the pathogenesis of allergic diseases; however, little is known about internal factors such as the biometrical structure of the eye. We investigated the relationship between refractive error and allergic conjunctivitis in order to reveal possible insights into the pathogenesis in 1015 subjects. Methods The patients were divided into four groups: contact lens wearers with allergic conjunctivitis (n ¼ 73), contact lens wearers without allergic conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…AC was significantly more prevalent in the younger age groups, showing a prevalence of 38.4% in those aged 0−16 years and least in the age group above 50 years (4.9%). This is similar to findings in previous studies that noted AC as one of the most frequent paediatric presentation to most out-patient eye units in Africa and countries with hot climates 121314151920212324252627. AC is shown to affect children from about age three and usually gets resolved by puberty.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…AC was significantly more prevalent in the younger age groups, showing a prevalence of 38.4% in those aged 0−16 years and least in the age group above 50 years (4.9%). This is similar to findings in previous studies that noted AC as one of the most frequent paediatric presentation to most out-patient eye units in Africa and countries with hot climates 121314151920212324252627. AC is shown to affect children from about age three and usually gets resolved by puberty.…”
Section: Discussionsupporting
confidence: 91%
“…The most prevalent ocular comorbid condition was refractive error in 15.4%. Mimura et al .,26 found 22.1% patients with AC had RE and postulated that RE could be a risk factor for AC. Wade et al ., also found RE to be the most common associated ocular morbidity.…”
Section: Discussionmentioning
confidence: 98%
“…In a fascinating study from Japan, Mimura and colleagues [21] have demonstrated that patients with SAC are more myopic than healthy individuals. Myopic eyes have a longer axial eye length and wider palpebral fissures and this may allow more conjunctival allergen exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The association of refractive errors, such as those occurring in keratoconus with vernal keratoconjunctivitis, is also known 2,5–7 . Furthermore, we previously reported that refractive errors are a risk factor for allergic conjunctivitis 8 . Allergens can cause various symptoms, among which allergic conjunctivitis is the commonest manifestation 9–10 .…”
Section: Introductionmentioning
confidence: 99%